Analysis of the Attitude And Learning Interest of Senior High School Students Towards Biology Lesson - Rangkuti, Ayu Septianty; Ulfa, Syarifah Widya (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Attitude is something that is needed by students because attitudes will affect student learning outcomes, while interest is a driving force for students to do what they expect. This study has the aim of knowing and analyzing the attitudes and interests of students to the subject of biology in high school students. On attitude by using indicators of cognitive, affective and conative views. In contrast to interest by using indicators of feelings of pleasure, attention, interest, and student involvement. This research was carried out at Senior High School of SMA Negeri 13 Medan in 2022 in May. This research is a qualitative descriptive study using observations, interviews, questionnaires, and documentation. The population of this research were students of Senior High School SMA Negeri 13 Medan by citing a sample of 90 students in class XI. The research instrument used was an attitude and interest questionnaire that explained attitudes towards learning biology through 3 indicators with 30 statements, then interest in learning biology through 4 indicators with 30 statements. The information analysis method used is descriptive statistics. This data analysis technique uses Miles & Hubermaan analysis which consists of three stages, namely data reduction, data presentation, and drawing and conclusions. Based on the results of the analysis of information, it was found that the students' actions and interest in learning atÂ Senior High School of SMA Negeri 13 Medan were in the strong category